Mortalidad de la fauna silvestre por efecto vehicular en la carretera Calceta-Quiroga - Gaón Rojas, John Estalin (2021)
The present work aimed to evaluate the mortality of wildlife due to vehicular effects on the Calceta-Quiroga highway in the last quarter of 2020; a 10 km stretch was monitored where 321 individuals were run over, composed of 55% amphibians, 19% mammals, 17% birds and 9% reptiles. The most affected species was the Veracruz Giant Toad (Rhinella horribilis) belonging to the Bufonidae family; however, Peter's running snake (Coniophanes dromiciformis) is the only species found to be in the vulnerable category (VU) on the red list. IUCN. The number of records determined a spatial run-over rate of 0.53 ind / Km * day; the spatial distribution determined that the kilometers of high incidence of accidents are: B, C, D, and E; in section D of the road there are the largest number of species run over, using the “Kernel Density” tool it was determined that this section presents two points of greater importance where 19 or more individuals died. Through a road audit, the existence of regulatory and precautionary traffic signs was identified, however, there is no presence of signs directed to the fauna conservation. The measurements were taken based on the site conditions, mostly measurements made up of speed bumps and underpasses of fauna complemented with their respective signaling; in addition, the maintenance of signs, the removal of vegetation, reforestation of the road margins, and environmental education.